Acid Mine Drainage Treatment With Zeolite And Red Gypsum At Tasik Puteri, Dungun, Terengganu - Johari, Adliwafi (Universiti Sains Malaysia, 2017)
Acid mine drainage is one of the main issue faced by mines worldwide. This is due to the health effects and environmental problem it may bring to its’ surrounding. The most particular reason is that it affect soil, aquatic life, plantations and can also cause acid rain. This will severely affect local’s economy and livelihood. While hydrated lime can neutralize the acid mine drainage to national water quality standard, exothermic reaction of lime when reacted with water can harm the lake ecological system. This thesis present the result of study conducted in Tasik Puteri, Dungun, Terrenganu to test zeolite and red gypsum to be used as alternative to treat AMD affected water source. Water sample are taken from Tasik Puteri with in-situ data. Experiment are conducted in lab using column test. A multimeter are used to collect data on AMD sample before and after column test. Plus, ICP-AES test also conducted on AMD sample before and after column test. Zeolite and red gypsum are studied with XRF to investigate their absorbent properties and analyse their elements. National water quality standard are used to compare the result from the column test. AMD treatment with zeolites are show promising result on pH value, but failed to neutralize one of the heavy metal present in the AMD sample. While, red gypsum unable to critically affect the AMD sample.